# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = 4 y
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y
\] |
✓ |
✓ |
|
\[
{}\left (x -2\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x -1\right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 \left (1+x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -1\right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 \left (x -1\right ) y^{\prime } = 3 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 4 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y = 0
\] |
✓ |
✗ |
|
\[
{}x^{3} y^{\prime } = 2 y
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x^{2} y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y^{\prime }+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = y
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+4 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+2\right ) y^{\prime \prime }+4 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+6 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-3\right ) y^{\prime \prime }+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }-6 x y^{\prime }+12 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+3\right ) y^{\prime \prime }-7 x y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+2\right ) y^{\prime \prime }-x y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+8 x y^{\prime }+12 y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime }+x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}5 y^{\prime \prime }-2 x y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y^{\prime }-3 x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left (x -1\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+2 x \right ) y^{\prime \prime }-6 \left (x -1\right ) y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-6 x +10\right ) y^{\prime \prime }-4 \left (x -3\right ) y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (4 x^{2}+16 x +17\right ) y^{\prime \prime } = 8 y
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+6 x \right ) y^{\prime \prime }+\left (3 x +9\right ) y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+2 x y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y^{\prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+1\right ) y^{\prime \prime }+x^{4} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y^{\prime }+\left (2 x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+{\mathrm e}^{-x} y = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +\sin \left (x \right ) y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 x y^{\prime }+2 \alpha y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +\left (-x^{3}+x \right ) y^{\prime }+y \sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +x^{2} y^{\prime }+\left ({\mathrm e}^{x}-1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\cos \left (x \right ) y^{\prime }+x y = 0
\] |
✓ |
✗ |
|
\[
{}3 x^{3} y^{\prime \prime }+2 x^{2} y^{\prime }+\left (-x^{2}+1\right ) y = 0
\] |
✓ |
✗ |
|
\[
{}x \left (1+x \right ) y^{\prime \prime }+2 y^{\prime }+3 x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (-x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+6 \sin \left (x \right ) y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x^{3}+6 x^{2}\right ) y^{\prime \prime }+21 x y^{\prime }+9 \left (x^{2}-1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime \prime }+x y^{\prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right )^{2} y^{\prime \prime }+\left (2 x -2\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+12 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -2\right )^{3} y^{\prime \prime }+3 \left (x -2\right )^{2} y^{\prime }+x^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-4\right ) y^{\prime \prime }+\left (x -2\right ) y^{\prime }+\left (x +2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-9\right )^{2} y^{\prime \prime }+\left (x^{2}+9\right ) y^{\prime }+\left (x^{2}+4\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -2\right )^{2} y^{\prime \prime }-\left (x^{2}-4\right ) y^{\prime }+\left (x +2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} \left (1-x \right ) y^{\prime \prime }+\left (3 x +2\right ) y^{\prime }+x y = 0
\] |
✓ |
✗ |
|
\[
{}4 y^{\prime \prime } x +2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime } x +3 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime } x -y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime } x +2 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+x y^{\prime }-\left (2 x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+x y^{\prime }-\left (-2 x^{2}+3\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}6 x^{2} y^{\prime \prime }+7 x y^{\prime }-\left (x^{2}+2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{\prime \prime }+2 x y^{\prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime } x +\left (1+x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime } x +\left (-2 x^{2}+1\right ) y^{\prime }-4 x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +2 y^{\prime }+9 x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +2 y^{\prime }-4 x y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime } x +8 y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x -y^{\prime }+4 x^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (-4 x^{2}+3\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+x \left (1+x \right ) y^{\prime }-\left (2 x +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (5 x^{3}+2 x^{2}\right ) y^{\prime \prime }+\left (-x^{2}+3 x \right ) y^{\prime }-\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+\sin \left (x \right ) y^{\prime }-y \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (3 x -1\right ) y^{\prime }+y = 0
\] |
✓ |
✗ |
|
\[
{}x^{3} y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✗ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (1-x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (x -1\right ) \left (1+x \right )^{2} y^{\prime \prime }+2 x \left (x -3\right ) \left (1+x \right ) y^{\prime }-2 \left (x -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (1-x \right ) y^{\prime \prime }+\left (\gamma -\left (\alpha +\beta +1\right ) x \right ) y^{\prime }-\alpha \beta y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +\left (3-x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +\left (5-x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } x +\left (3 x +5\right ) y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|